Large outbreak of multiple gastrointestinal pathogens associated with fresh curry leaves in North East England, 2013. Issue 15 (15th August 2018) - Waldram, A.; Lawler, J.; Jenkins, C.; Collins, J.; Payne, M.; Aird, H.; Swindlehurst, M.; Adak, G. K.; Grant, K.; Ready, D.; Gorton, R.; Foster, K.
Abstract: A total of 592 people reported gastrointestinal illness following attendance at Street Spice, a food festival held in Newcastle-upon-Tyne, North East England in February/March 2013. Epidemiological, microbiological and environmental investigations were undertaken to identify the source and prevent further cases. Several epidemiological analyses were conducted; a cohort study; a follow-up survey of cases and capture re-capture to estimate the true burden of cases. Indistinguishable isolates of Salmonella Agona phage type 40 were identified in cases and on fresh curry leaves used in one of the accompaniments served at the event. Molecular testing indicated entero-aggregative Escherichia coli and Shigella also contributed to the burden of illness. Analytical studies found strong associations between illness and eating food from a particular stall and with food items including coconut chutney which contained fresh curry leaves. Further investigation of the food supply chain and food preparation techniques identified a lack of clear instruction on the use of fresh uncooked curry leaves in finished dishes and uncertainty about their status as a ready-to-eat product. We describe the investigation of one of the largest outbreaks of food poisoning in England, involving several gastrointestinal pathogens including a strain of Salmonella Agona not previously seen in the UK.